Pengaruh Kurikulum Merdeka terhadap Kreativitas dan Inovasi Peserta Didik dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti - Putri Anisah Nasution; Rukiah Rukiah; Siti Aisyah; Jamilatun Rohmah Siregar (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the significant influence of the merdeka curriculum on students’ creativity and innovation in Islamic education and character education (pai-bp) learning at SMA Negeri 2 Plus Panyabungan. The importance of creating a learning process that encourages students to think creatively and act innovatively, especially in PAI-BP subjects that play a strategic role in shaping students’ character and morals. The research method used is a quantitative approach with a correlational design. The sample consisted of 63 students selected through a simple random sampling technique. Data were collected using a likert-scale questionnaire. Validity and reliability tests indicated that all research instrument items were valid and reliable. Data analysis was conducted using descriptive statistics, classical assumption tests, pearson correlation tests, and simple linear regression analysis. The results of this study show a strong and significant relationship between the merdeka curriculum and students’ creativity and innovation, with a correlation coefficient of 0,780 and a significance value of 0,000. The R-square value of 60.8% indicates that the merdeka curriculum contributes 60,8% to the improvement of creativity and innovation in PAI-BP learning.